LABOUR PROTECTION SPECIALISTS COMPETENCE MODEL - Brizga, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The number of fatal accidents in the workplace in Latvia in 2014 was higher than the average in the European Union and continues to grow. One remedial action for preventing accidents is to improve the competence of labour protection specialists. The aim of this study was to evaluate and improve a competence development model for labour protection specialists, as well as to make an expert assessment of the model. This was carried out by experts with experience in the implementation of educational programs and other professional activities. The experts ranked highly all the parameters of the model and determined that the competence model would be useful for improving labour protection and other specialists’ training, study and practice.